Beyond Communitarianism
IX, 226 p.
Keywords: This book investigates different notions of communitarianism and citizenship, and their application within a number of fields, in particular education, politics and social welfare. Whilst there can be no doubt that most observers regard the responsible conduct of citizens as a goal worth pursuing, difficult problems lie with questions of how, and indeed whether, responsible citizenship can be achieved. This book looks beyond communitarian ideology to investigate more detailed discussion of citizenship in contemporary society.